Étudiants arabophones de retour à Ouagadougou cherchent désespérément reconnaissance - Sylvie Bredeloup (L’Année du Maghreb)
The returning graduates from the Arabic modernised education system, trained in the universities of the Arab-Islamic world struggle to find a place in Burkina Faso. Interviews of students returning to Ouagadougou after several years spent studying in Islamic universities (in Egypt, Algeria, Saudi Arabia or Libya) will allow us to look at how the academic profiles of these students, shaped by the historical and political context as well as by their existential motivations have affected their professional careers. Parental injunctions and grants have mostly determined the place of study and the subjects, taking part in shaping the professional trajectory. For most, studies turned out to be lengthy and chaotic, and professional opportunities after their return seldom matched the training they had received. Reintegrating these students into the Burkinabè society is problematic. They do not always master French, the official language, and are often excluded from the labour market. They have failed to put pressure on their government for recognition of their diplomas. And they suffer from a denial of recognition that does not lead to open protest.